Brief communication: body composition and hidden obesity in people living with HIV on antiretroviral therapy - K. Konishi; H. Nakagawa; T. Asaoka; Y. Kasamatsu; T. Goto; M. Shirano (AIDS Research and Therapy, 2024)
Abstract Background Increased incidence of lifestyle diseases as side-effects of antiretroviral therapy (ART) have been reported in people living with HIV (PLWH). Few studies have evaluated obesity and hidden obesity in Japanese PLWH and their association with ART. In order to provide more appropriate drug selection and lifestyle guidance, we investigated the relationship between the effects of HIV infection and ART on the body composition of Japanese PLWH. Methods PLWH who visited the outpatient clinic and had body composition measured using the body composition analyzer InBody 570 were included in this study. Medications, comorbidities, and blood test data were obtained. Body mass index (BMI), body fat percentage, and skeletal muscle mass index (SMI) were measured. Results In this study, 543 patients were included. Based on body shape, patients were classified into a thin group (13), normal weight group (14), hidden obesity group (158), apparent obesity group (14), and obesity group (218). Compared with the normal weight group, the hidden obesity group had a higher prevalence of comorbidities and a lower SMI. Conclusions PLWH are more likely to have obesity than the general population, indicating that hidden obesity is common even among those with a normal BMI. It is important to measure body fat percentage along with body weight, as hidden obesity can be missed. Further investigation of the effects of ART on body composition is needed.